2008
DOI: 10.1211/jpp.60.10.0001
|View full text |Cite
|
Sign up to set email alerts
|

Formed and preformed metabolites: facts and comparisons

Abstract: The administration of metabolites arising from new drug entities is often employed in drug discovery to investigate their associated toxicity. It is expected that administration of metabolites can predict the exposure of metabolites originating from the administration of precursor drug. Whether exact and meaningful information can be obtained from this has been a topic of debate. This communication summarizes observations and theoretical relationships based on physiological modelling for the liver, kidney and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 166 publications
1
35
0
Order By: Relevance
“…However, most of the focus was on precursor-metabolite pairs that undergo irreversible metabolism, and AUC R {mi,P} of the formed metabolite was found to be modulated by eliminatory parameters of the precursor and not vice versa (de Lannoy et al, 1993;Pang et al, 2008) (Tables 1 and 2 when CL int,met Mi3 D {mi} ϭ 0). Upon incorporation of interconversion between the precursor and metabolite and alternate metabolic pathways in present PBPK model, we provided analytical solutions and showed that, in the presence of futile cycling, the eliminatory parameters of the metabolite would affect the disposition of the precursor (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the focus was on precursor-metabolite pairs that undergo irreversible metabolism, and AUC R {mi,P} of the formed metabolite was found to be modulated by eliminatory parameters of the precursor and not vice versa (de Lannoy et al, 1993;Pang et al, 2008) (Tables 1 and 2 when CL int,met Mi3 D {mi} ϭ 0). Upon incorporation of interconversion between the precursor and metabolite and alternate metabolic pathways in present PBPK model, we provided analytical solutions and showed that, in the presence of futile cycling, the eliminatory parameters of the metabolite would affect the disposition of the precursor (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Ordinarily, metabolite parameters would not have an impact on parent drug processing (Pang et al, 2008). However, metabolite and drug parameters do affect the net metabolism, via the coefficient, ef m Ј, when futile cycling exists (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that, generally, compartmental modeling is unable to quantitatively address the multiplicity of metabolite formation organs and does not account for sequential metabolism/excretion nor permeability barriers of formed metabolites (Pang et al, 2008;Pang, 2009). In contrast, physiologically based pharmacokinetic (PBPK) models address events of sequential elimination and include transmembrane barriers Pang, 1986, 1993;Pang, 2003;Pang et al, 2009;Chow and Pang, 2013) and transporters (Sun et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Compartmental models are no longer adequate to address effects of permeability barriers Pang, 1986, 1987), intestinal and liver transporters and enzymes (Suzuki and Sugiyama, 2000a,b), and sequential metabolism within the intestine and liver (Pang and Gillette, 1979;Sun and Pang, 2010) during oral drug absorption (for reviews, see Pang, 2003;Pang et al, 2008;Fan et al, 2010;Pang and Durk, 2010;Chow and Pang, 2013). These aspects are especially pertinent when intestinal metabolic activity is substantial relative to that in the liver, and when different extents of induction/inhibition of intestinal and hepatic enzymes or transporters are the result of treatment with the culprit compound, which usually shows a higher induction/inhibition effect with oral administration (Fromm et al, 1996;Paine et al, 1996;Thummel et al, 1996;Eeckhoudt et al, 2002;Mouly et al, 2002;Fang and Zhang, 2010;Liu et al, 2010;Lledó-García et al, 2011;Zhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These three intestinal models are viewed as competent to describe the immediate removal of the formed metabolite by excretion or sequential metabolism within the intestine and/or further processing by liver, for drugs and metabolites exhibiting varying permeability properties (Cong et al, 2000;Yang et al, 2006Yang et al, , 2007Gertz et al, 2010;Sun and Pang, 2010). The models are more prepared to supply mechanistic insight into the pharmacokinetics of drugs and their metabolites and allow inclusion of transporters into different organ components (apical or basolateral membranes) to discriminate between the permeability properties of the drug and its formed metabolite in permitting or delimiting influx and efflux in drug and metabolite processing (Pang et al, 2008;Darwich et al, 2010;Galetin et al, 2010;Gertz et al, 2010;Rowland Yeo et al, 2010;Chow and Pang, 2013). By virtue of inclusion of transport and eliminatory events, these physiologically based models are able to more accurately describe the net appearance of the formed metabolite into the systemic circulation, because metabolite levels can be drastically reduced as a result of sequential metabolism (Pang and Gillette, 1979).…”
Section: Introductionmentioning
confidence: 99%